A New Experimental Method to Determine the Henry’s Law Constant of a Volatile Organic Compound Adsorbed in Soil - S. Ouoba; F. Cherblanc; J. Koulidiati; J.-C. Bénet (Journal of Chemistry)
This paper presents a new mechanical method to determine Henry’s law constant (HLC) of a volatile organic compound (VOC). This method is an extension of the one proposed by Ouoba et al. (2010) to determine the water activity in porous media. This work focuses on TCE and aims at characterizing its liquid-vapor equilibrium in various cases in the form of a pure liquid phase or dissolved in an aqueous solution, adsorbed or not in a natural soil. A liquid phase is disposed in a closed chamber whose volume can be incrementally increased. The recording of the total gas pressure leads to evaluating the vapor partial pressure of a volatile compound even in the case of an aqueous solution. This method has been validated using various aqueous solutions of TCE and the HLC obtained is in agreement with the literature. Then, the validity of Henry’s law has been asserted in the case of an aqueous solution of TCE adsorbed in a hygroscopic soil. Indeed, a linear relation between the vapor partial pressure of TCE and its concentration has been obtained while the HLC is about 16% lower. This result highlights the influence of adsorption phenomena on vapor/liquid equilibrium.